FOPID Controlled Three Stage Interleaved Boost Converter Fed DC Motor Drive - M.L Bharathi; D. Kirubakaran (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Three stage Interleaved boost converter is a good choice between DC source and DC motor. This work deals with enhancement of response of three stage ILBC fed DC motor drive system using FOPID controller. Closed loop ILBCDCM systems controlled by PI & FOPID are modeled and simulated. The results are presented for PI & FOPID controlled ILBCDCM systems. The comparison of response is done in terms of settling time and steady state error in speed of ILBCDCM. The results indicate that FOPID controlled ILBCDCM gives better response than PI controlled ILBCDCM system.